2016
DOI: 10.1002/jso.24418
|View full text |Cite
|
Sign up to set email alerts
|

Oncofertility program implementation increases access to fertility preservation options and assisted reproductive procedures for breast cancer patients

Abstract: Background and Objectives Breast cancer treatment can cause premature ovarian failure, yet the majority of young cancer patients do not receive adequate education about treatment effects before initiating chemotherapy. We studied the impact of an oncofertility program on access to fertility preservation. Methods An oncofertility program was initiated to foster collaboration between oncologists and reproductive endocrinologists, and to help increase access to fertility preservation. Documented conversations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 36 publications
2
50
0
Order By: Relevance
“…One possible interpretation of the present result is that those physicians working at a cancer clinic that is geographically and organizationally close to a reproduction clinic are more likely to refer such discussions to fertility specialists, instead of having them directly with their patients. A multifaceted oncofertility program including both organizational and educational interventions has recently been shown to increase the frequency of documented fertility-related conversations between oncologists and patients, as well as referral rates to reproductive endocrinology and/or FP [24]. This strengthens the conclusion that, despite relatively high levels of perceived knowledge about treatment-related infertility risks among Swedish oncologists and hematologists, identifying and eliminating organizational barriers could be helpful in order to further improve fertility-related communication in cancer care.…”
Section: Discussionmentioning
confidence: 62%
“…One possible interpretation of the present result is that those physicians working at a cancer clinic that is geographically and organizationally close to a reproduction clinic are more likely to refer such discussions to fertility specialists, instead of having them directly with their patients. A multifaceted oncofertility program including both organizational and educational interventions has recently been shown to increase the frequency of documented fertility-related conversations between oncologists and patients, as well as referral rates to reproductive endocrinology and/or FP [24]. This strengthens the conclusion that, despite relatively high levels of perceived knowledge about treatment-related infertility risks among Swedish oncologists and hematologists, identifying and eliminating organizational barriers could be helpful in order to further improve fertility-related communication in cancer care.…”
Section: Discussionmentioning
confidence: 62%
“…A recent review, identified eight established oncofertility models of care and their key components including clinician education about FP, collaboration with fertility specialists, established referral pathways, educational materials for patients, patient navigator and electronic notification. Promising results indicate that implementation of a multifaceted oncofertility program increased the frequency of documented fertility‐related discussions as well as referral rates to fertility specialists and the use of FP . The development and implementation of multifaceted oncofertility programs appears to be a promising way forward towards high‐quality FP care meeting patients' needs.…”
Section: Resultsmentioning
confidence: 99%
“…A recent review, 34 iden- to fertility specialists and the use of FP. 35 The development and implementation of multifaceted oncofertility programs appears to be a promising way forward towards high-quality FP care meeting patients' needs.…”
Section: Con Clus Ionmentioning
confidence: 99%
“…Communication about fertility preservation options and appropriate referral to a specialist are both critical to quality of life of young BC patients and may also impact disease outcomes 38 . Women who received a cancer diagnosis have indicated that the feeling of distress associated with the threat to fertility posed by cancer treatment was on par with the distress associated with BC diagnosis 39 .…”
Section: Fertilitymentioning
confidence: 99%